Evaluation of injury threshold from the number of rib fracture for predicting pulmonary injuries in blunt chest trauma. Issue 4 (April 2023) - Fukushima, Kazunori; Kambe, Masahiko; Aramaki, Yuto; Ichikawa, Yumi; Isshiki, Yuta; Nakajima, Jun; Sawada, Yusuke; Oshima, Kiyohiro
Abstract: Background: Blunt chest trauma is a common presentation in emergency departments. The relationship between bone fractures and organ injuries has not been studied in detail. The purpose of this study was to examine the degree of external force represented by the number of rib fractures that causes lung injury in blunt chest trauma. Patients and methods: This study was performed retrospectively using trauma patients who received medical examinations in a single university hospital emergency center between April 2015 and March 2020. We examined the association between the number of rib fractures and pulmonary damage using multivariable regression analysis and considered the relationship between rib fracture location and each type of lung injury. Results: A total of 317 patients were included. The mean age was 63.1 years, 65.0% were male, and traffic accidents were the most common mechanism of injury (55.8%). The number of mean rib fractures was 4.0, and the mean Injury Severity Score was 11.3. The number of rib fractures was associated with an increased risk of pulmonary injuries: pulmonary contusion (odds ratio [OR] 1.30, 95% confidence interval [CI] 1.14–1.48, p < 0.05); hemothorax (OR 1.22, 95% CI 1.08–1.38, p < 0.05); pneumothorax (OR 1.15, 95% CI 1.02–1.30, p < 0.05); and hemopneumothorax (OR 1.14, 95% CI 1.01–1.28, p < 0.05). In addition, bilateral rib fractures were associated with fractures of the superior ribs more often and more severely, but were not associated with the occurrence of each type of lung injury. Conclusion: The number of rib fractures was associated with an increased risk of pulmonary injuries. In addition, the type of pulmonary injury could be predicted from the number of rib fractures in blunt chest trauma.